2018
DOI: 10.1007/s00038-018-1166-7
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette use is associated with other tobacco use among US adolescents

Abstract: Objectives To examine whether tobacco initiation via e-cigarettes increases the likelihood of subsequent tobacco use among a large representative sample of US adolescents. Methods This study is a retrospective longitudinal analysis from a representative sample of US middle and high school students (n = 39,718) who completed the 2014 and 2015 National Youth Tobacco Survey. The adjusted odds ratios of lifetime and current use of tobacco use were estimated by logistic regression analysis while controlling for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…The quality of studies (or inversely, risk of bias) was good in most cases when rated using the NOS (online supplementary table S2). One study was rated as fair quality,18 and three were rated as poor quality 13 19 20. Of the four Bradford-Hill criteria for causality deemed relevant to this research, the majority (11 studies) met three criteria (usually strength of evidence, temporality and specificity), 4 studies only met two criteria6 9 10 19 and 2 met four criteria 13 14…”
Section: Resultsmentioning
confidence: 99%
“…The quality of studies (or inversely, risk of bias) was good in most cases when rated using the NOS (online supplementary table S2). One study was rated as fair quality,18 and three were rated as poor quality 13 19 20. Of the four Bradford-Hill criteria for causality deemed relevant to this research, the majority (11 studies) met three criteria (usually strength of evidence, temporality and specificity), 4 studies only met two criteria6 9 10 19 and 2 met four criteria 13 14…”
Section: Resultsmentioning
confidence: 99%
“…Results were separated based on these three categories and combined with the 13 primary research studies identified in the umbrella review. Twelve of the seventeen studies in Khouja et al were included, 20 31 33-42 three were excluded due to data overlap, [52][53][54] one was excluded as it used retrospective data 55 and one was excluded as it was cross-sectional. 56 Of the eight studies in Aladeokin and Haighton, two were included 39 40 ; five were excluded for cross-sectional design [57][58][59][60][61] and one for data overlap.…”
Section: Umbrella Reviewmentioning
confidence: 99%
“…Thus, changing to smoking could be explained by youth experimentation and propensity to risk (314,315). Concurrent use of nicotine products has also been reported by AUF et al (316). However, national surveys do not suggest any gateway effect.…”
Section: Vapers Demographics -Uptake By Young People and Potential Gateway Effectsmentioning
confidence: 83%